Adesão borracha-latão: a influência do cobalto, do sistema HMMM (hexametoximetilmelamina)-resorcinol e da temperatura na interface - Viana, Roni Carlos (Universidade Federal de São Carlos, 2006)
Using a blank compound as reference and brass coated steel tire cords with 64 and 68.2 % of cooper content, it was studied the effect of the ingredients cobalt and the HMMM-resorcinol system, and the vulcanization temperature on the rubber-brass adhesion. Samples were studied as new (original), aged in oven, steam and humidity environments. Mechanical properties, vulcanization kinetics and cross linking density were analyzed in the compounds. The ingredients, as well as the vulcanization temperature, showed a strong effect on the compounds properties, however, it did not show relation with the adhesion. The steel tire cords were evaluated by scanning electron microscopy (SEM) and energy dispersive x-ray spectroscopy (EDS), being evident variations on brass deposition, which can lead to adhesion loss. The adhesion of the samples was evaluated by means of the force and coverage by pull out tests from a rubber block. The results, for each condition, were statistically analyzed. For the original condition, the steel cord with high content of cooper (68.2 %) showed higher adhesion values. In oven, only the effect of HMMM-resorcinol system was statistically significant. Aging in steam, the most aggressive condition, showed that the use of cobalt was effective in the maintenance of the adhesion level. Aging with humidity showed that the adhesion promoters cobalt and HMMM-resorcinol system were beneficial to the rubber-brass adhesion. The cords surface, after the extraction of the rubber, was evaluated by SEM and EDS. The formation of a CuxS structure, responsible for rubber-brass adhesion was evident. In general, it was not found a unique combination which guaranteed the maximum adhesion level for the studied conditions, however, the better balance was achieved using a steel cord with 64 % of cooper, the adhesion promoters cobalt and HMMM-resorcinol system, and the vulcanization temperature of 150 ºC.
Rubber-brass adhesion to tire steel cords- the influence of cobalt, the HMMM (Hexamethoxymethylmelamine)-resorcinol system and the temperature at the interface
Keywords: Adesão borracha-latão; Borracha; Interface; Metal - superfície; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA